2019
DOI: 10.3389/fmicb.2019.02167
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analyses of Some Melanoleuca Species (Agaricales, Tricholomataceae) in Northern China, With Descriptions of Two New Species and the Identification of Seven Species as a First Record

Abstract: Two new species (Melanoleuca galerina and M. subgrammopodia) and seven new recorded species from northern China are described here using morphological and molecular methods. Melanoleuca galerina is mainly characterized by its hygrophanous pileus, decurrent lamellae, fibrous stipe and spores with round warts. Key characteristics of M. subgrammopodia include its discolored pileus, fibrous stipe and urticiform cystidia. The divergence time of Melanoleuca fungi as well as the phylogenetic relationships within this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Melanoleuca Vizzini. Then, follow-up studies on species of Melanoleuca support the classification opinion proposed by Vizzini et al (2011) ( Yu et al, 2014 ; Kalmer, Acar & Dizkirici, 2018 ; Xu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Melanoleuca Vizzini. Then, follow-up studies on species of Melanoleuca support the classification opinion proposed by Vizzini et al (2011) ( Yu et al, 2014 ; Kalmer, Acar & Dizkirici, 2018 ; Xu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 60%
“…Konrad & Maubl etc. Recently, many new species of Melanoleuca have been reported throughout the world ( Vizzini et al, 2010 ; Vizzini et al, 2011 ; Sánchez-García, Cifuentes-Blanco & Matheny, 2013 ; Antonín et al, 2014 ; Antonín et al, 2017 ; Antonín et al, 2021 ; Yu et al, 2014 ; Nawaz, Jabeen & Khalid, 2017 ; Xu et al, 2019 ; Pei et al, 2021 ). Melanoleuca is a taxonomically complicated genus because many species in the genus are very similar in macroscopical characteristics and only present subtle differences ( Bon, 1991 ; Boekhout, 1999 ; Vizzini et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factor Q is the value of its length divided by width and Qm is the mean of the Q values. The procedure for scanning electron microscopy (SEM) followed that of Xu et al [29], and an FEI Quanta 200FE-SEM (JEOL Ltd., Akishima, Japan) was used at an accelerating voltage of 5-10 kV.…”
Section: Morphological Observationmentioning
confidence: 99%
“…& Pouzar and Amanitaceae E.-J. Gilbert (Moncalvo et al 2002;Matheny et al 2006;Garnica et al 2007;Justo et al 2011;Vizzini et al 2011;Sánchez-García et al 2014;Antonín et al, 2014Antonín et al, , 2017Antonín et al, , 2021Binder et al 2014;Yu et al 2014;Kalmer et al, 2018;Xu et al, 2019;Pei et al, 2021). Vizzini et al (2011) revealed that Melanoleuca is monophyletic, and divided into two subgenera, subg.…”
Section: Introductionmentioning
confidence: 99%